Audit Energi dan Penilaian Kualitas Daya Pada Penerangan Jalan Umum Politeknik Negeri Malang - Ahmad Hermawan; Galih Hardika Sakti; Ferdian Ronilaya; Satria Luthfi Hermawan (Elposys: Jurnal Sistem Kelistrikan, 2022)
Public Street Lighting (PSL) is an important thing for campus residents especially in night time activities. PJU also function as the beauty and comfort of college student when doing activities / organization at night and also influencing the results of carried active by college student. PSL also serve to ease visions for campus guard so that it is easier to see or supervise the area around the campus from thieves or individuals who want to behave crimefully at State Polytechnic of Malang